PERLINDUNGAN HUKUM ATAS HAK MEREK(Studi Kasus Merek Spesial Sambal "SS" dalam Sengketa Passing Off) - Heriyanto, Doni, Inayah, S.H, M.H (2017)
Trademark rights related to law Number 15 of 2001 on the brand, it can be concluded that is entitled to the legal protections of passing off the first user and regristrant on the brand used. Brand is a form of intellectual property that is used to identify and distinguish goods or services. However, the brand is very vulnerable imitade by unscrupulous parties. The imitation brands such as passing off impact on the loss of material and nonmaterial.Against an infringer of the brand, trademark rights holders can safeguard in law No. 15 of 2001. One of remedy applied is through arbitration or alternative of dispute resolution. The resulted of the decision is cessation off all acts relating to the use of brand imitated.